Associations of specific and multiple types of childhood abuse and neglect with personality pathology among adolescents referred for mental health services. (December 2018) - Charak, Ruby; Tromp, Noor B.; Koot, Hans M.
Highlights: Non-sexual abuse types such as, emotional and physical abuses are uniquely associated with personality pathology traits. Based on exposure to childhood maltreatment types, three latent classes, differing in maltreatment types and severity emerge in a treatment-seeking sample of adolescents. Latent classes with exposure to more types of maltreatment and higher severity were higher on traits of personality pathology, personality disorder symptom counts, and diagnosed personality disorders. Abstract: The present study investigated the unique association between five types of childhood abuse and neglect and 18 lower-order dimensions of personality pathology, and using latent classes analysis (LCA) explored patterns of childhood abuse or neglect experiences. Further differences across latent classes on personality pathology traits, personality disorder symptom count and a diagnosis of personality disorder were examined. Participants were 178 adolescents and young adults (12–22 years; M  = 16.02, 65.7% girls; 83% Axis I/II disorder) from the Netherlands referred for mental health services. Emotional abuse was uniquely associated with 11 personality pathology traits; sexual and physical were associated with three and four traits, respectively. LCA yielded three classes, namely, severe maltreatment (class 1), low-moderate emotional maltreatment and sexual abuse (class 2), and least maltreatment (class 3) . After controlling for age, gender, presence of any Axis I disorder, multivariate analysis of covariance indicated that classes with more types of maltreatment experiences and higher severity (classes 1 and 2) endorsed more personality pathology traits, personality disorder symptom counts and a diagnosis of a personality disorder than the least maltreatment class. Findings have theoretical and clinical implications entailing the identification of patterns of maltreatment types and related personality pathology traits among youth.